Rancang Bangun Sistem Informasi Nilai Mata Pelajaran Berbasis Web dan SMS Gateway - Akhsin Rifai; Hindayati Mustafidah (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2013)
Score at the agency school is one measure of the success of students in learning the material presented. To provide score transparency to students and parents needed an information system score subjects in an easy and fast data access. In fulfilling these conditions, build-up lesson score information system of Web and SMS Gateway Based. The system is built using Gammu software and using the programming language PHP. By using SMS to obtain the score of the data is expected to provide convenience for parents to monitor learning outcomes of their children’s in school.